RUS TÜRKOLOGLARINA GÖRE GÜNEYBATI (OĞUZ) TÜRK LEHÇELERİNDE TASARLAMA KİPLERİ - Kyzy, Lira Maırambek (Ahmet BURAN, 2022)
Türkçede kip kavramı bildirme ve tasarlama olmak üzere iki kategori altında ele alınır. Bildirme kipleri zaman anlamı veren yapıları kapsarken, tasarlama kipleri istek, emir, şart ve gereklilik bildiren yapıları içerir. Konuşurun eylem karşısındaki tutumunu, niyetini ve duygusunu belirten bu tasarlama kiplerinin bazen lehçeden lehçeye şekil, anlam ve işlev bakımından farklılık arzettiği, bazen de iç içe girdiği görülür. Bu çalışmada Baskakov, Kononov, Şçerbak, Serebrennikov, Gadjieva, Pokrovskaya, Grunina, Budagova, Guzev gibi Rus Türkologlarının güneybatı Türk lehçelerindeki tasarlama kiplerinin durumunu, yapılarını ve dildeki kullanımlarını değerlendiriş biçimleri ele alınacaktır.

Turkic moods are divided into two categories: indicative and irrealis. While indicative moods include structures that give meaning to time, irrealis moods contain structures that express request, order, condition and necessity. It has been observed that these irrealis moods which indicate the attitude, intent and emotion of the speaker against the action, sometimes vary from dialect to dialect in terms of form, meaning, and function, and sometimes intertwine with each other. This paper deals with how Russian Turkologists such as Baskakov, Kononov, Shcherbak, Serebrennikov, Gadzhieva Pokrovskaya, Grunina, Budagova, and Guzev have examined the state, structure, and use of irrealis moods in southwestern Turkic dialects.
Irrealis moods in southwestern (Oghuz) Turkic dialects according to Russian turkologist
Keywords: Linguistics; Dilbilim